2013
DOI: 10.1002/anie.201303288
|View full text |Cite
|
Sign up to set email alerts
|

Binary Genetic Cassettes for Selecting XNA‐Templated DNA Synthesis In Vivo

Abstract: Hereditary information, coded in two bases, can be conveyed to DNA in vivo in the form of cyclohexenyl nucleic acid (CeNA), arabinofuranosyl nucleic acid (AraNA), and hexitol nucleic acid (HNA) messages. It was thus demonstrated that a binary genetic cassette can be used for the title process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 27 publications
1
36
0
1
Order By: Relevance
“…[2] Another motivation for exploring chemical variants of nucleic acids has been the elaboration of possible scenarios for the origin of life. [3] More recently the chemical diversification of nucleic acids has been attempted in vivo to propagate additional types of nucleic acids (XNA) as templates for DNA synthesis in E. coli [4,5] and for transcription into RNAi n mammalian cells. [6] In addition, DNAw ith at riazole linker instead of aphosphodiester bound have been accepted by E. coli [7a,b] and human [7c] cells.I th as also been reported that as emisynthetic organism is able to replicate with as ingle unnatural base pair in vivo.…”
mentioning
confidence: 99%
“…[2] Another motivation for exploring chemical variants of nucleic acids has been the elaboration of possible scenarios for the origin of life. [3] More recently the chemical diversification of nucleic acids has been attempted in vivo to propagate additional types of nucleic acids (XNA) as templates for DNA synthesis in E. coli [4,5] and for transcription into RNAi n mammalian cells. [6] In addition, DNAw ith at riazole linker instead of aphosphodiester bound have been accepted by E. coli [7a,b] and human [7c] cells.I th as also been reported that as emisynthetic organism is able to replicate with as ingle unnatural base pair in vivo.…”
mentioning
confidence: 99%
“…In principle, such an “expanded chimeric‐repeat unit” strategy consisting of two isomeric cyclic‐sugars with differing chirality ( l ‐ribulose and d ‐ribose) and an acyclic (glycerol) unit, demonstrates a simple, yet viable potential of generating nucleic acid systems with diversified properties . For example, a functioning system based on a two‐letter code using only adenine and thymine can, in principle, potentially be developed, since it may be possible to mimic a four letter code (“GC” and “AU”). By using the stronger ribulo‐pyrimidine‐ribo‐purine ( r t ‐rA) combination, the “GC” unit can be impersonated, while the weaker ribulo‐purine‐ribo‐pyrimidine r a ‐rT combinations would simulate the “AU” unit.…”
Section: Discussionmentioning
confidence: 99%
“…Chem . 2013 ) . A mix of equimolar (25 ng each) purified NheI and NsiI cut pAK1 and purified EcoRI cut and dephosphorylated pAK2 were resuspended in 10 m m Tris‐HCl pH 7.5 with 100 m m NaCl in 20 μL final volume.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo transliteration and mutational analysis directedby modified oligonucleotides ligated to plasmid DNA Oligonucleotides were dissolved in milliQ water to 1mm and diluted ten fold before assay.O ligonucleotides were tested inside a gapped heteroduplex generated through the enzymatic modification of two different plasmids pAK1 and pAK2. The form of the heteroduplex is described elsewhere in details (S. Pochet, C. R. Biol. 2003 andPezo, Angew.C hem.…”
Section: Primer Extension Experiments By Dna Polymerasesmentioning
confidence: 99%